Profil Pengetahuan Dan Perilaku Pencegahan Diabetic Foot Ulcer Pada Pasien Diabetes Melitus Tipe II - Januar Ramadhan; Leni Merdawati; Hema Malini; Fitri Mailani (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Type 2 diabetes mellitus is a chronic condition associated with various complications, including diabetic foot ulcer (DFU). Adequate knowledge and appropriate preventive behaviors are essential in reducing the risk of DFU. This study aimed to describe the level of knowledge and preventive behaviors related to DFU among patients with type 2 diabetes mellitus. A descriptive quantitative design was employed using purposive sampling. A total of 32 patients who met the inclusion criteria participated in the study. Data were collected using structured questionnaires on DFU knowledge and preventive behaviors and analyzed descriptively. Most respondents were aged 30–65 years (62.5%), male (59.4%), had secondary education (46.9%), and had lived with diabetes for more than one year (65.6%). The mean score for DFU knowledge was 10.66 ± 3.347 (range 4–17), while the mean preventive behavior score was 15.31 ± 3.187 (range 6–20). Overall, respondents demonstrated good levels of knowledge and preventive behaviors. In conclusion, patients with type 2 diabetes mellitus showed relatively good knowledge and preventive behaviors regarding DFU. These findings highlight the importance of continuous foot care education to strengthen prevention strategies and reduce the risk of diabetes-related complications. Keywords: type 2 diabetes mellitus, diabetic foot ulcer, foot ulcer complications, knowledge, preventive behavior